Corynosoma australe Johnston, 1937 and C. cetaceum Johnston & Best, 1942 (Acanthocephala: Polymorphidae) from marine mammals and fishes in Argentinian waters: allozyme markers and taxonomic status - Sardella, Norma Haydee; Mattiucci, Simonetta; Timi, Juan Tomas; Bastida, Ricardo Oscar; Rodriguez, Diego Horacio; Nascetti, Giuseppe (Systematic Parasitology)
Genetic and morphological studies were carried out on acanthocephalans belonging to Corynosoma Lu¨he, 1904 and referable to the species C. cetaceum Johnston & Best, 1942 and C. australe Johnston, 1937, which were recovered from both definitive and intermediate hosts in Argentinian waters. The aims were to estimate the level of genetic differentiation between the two taxa at any stage of their life-cycle, to provide genetic (allozyme) markers for their recognition and to analyse the systematic status of both taxa. Acanthocephalans were collected from the stomach and intestine of Arctocephalus australis (Zimmerman), the intestine of Mirounga leonina (Linnaeus) and the stomach of Pontoporia blainvillei Gervais & D’Orbigny (definitive hosts) in Argentinian waters. Alternative alleles at all the 13 enzymatic loci studied were observed for C. australe and C. cetaceum. The specimens from the stomach of both P. blainvillei and A. australis were identified, on the basis of the great number of diagnostic loci found, as C. cetaceum; those from intestine of both A. australis and M. leonina as C. australe. A high level of genetic differentiation (DNei=¥: INei=0.00) between the two taxa was found, suggesting a generic distinction between the two species. Cystacanths of the two species from the body-cavity of the fish Cynoscion guatucupa (Cuvier) collected from the same geographical area were identified genetically. Morphological patterns, such as the number of hooks and hook rows on the proboscis, the distribution of somatic and genital armature, and other morphometric and meristic differences, in addition to ecological data, enabled the identification of these two species at cystacanth, juvenile and adult stages. However, a number of morphological and morphometric features of the Argentinian material were different to those of C. australe and C. cetaceum described from other regions of the world Fil: Sardella, Norma Haydee. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico ...